Selective laser melting of AlSi10Mg alloy: influence of heat treatment condition on mechanical properties and microstructure - Iturrioz, A.; Gil, E.; Petite, M. M.; Garciandia, F.; Mancisidor, A. M.; San Sebastian, M. (Welding in the world, 2018)
AlSi10Mg is the Al alloy most applied for selective laser melting (SLM) processing studies. The characteristics and the density obtained for SLM-processed material is extremely influenced by the quality of the starting powder. Since the microstructure obtained after SLM is often metastable, the required heat treatment to obtain an “optimized” microstructure can be significantly different than the one applied to conventionally cast or wrought Al alloys. In the present work, different thermal treatments have been applied to samples manufactured by SLM in order to investigate the effect on the microstructure and mechanical properties. The microstructural evaluation has been performed by SEM analysis and the mechanical properties have been determined by hardness measurements and tensile tests. Samples in the as-built condition, after stress relieving and under T6 heat treatment have been investigated to determine the best combination of properties.